ANALISIS BAURAN PEMASARAN UNTUK MENINGKATKAN PENDAPATAN PADA BENGKEL LAS IWAN BANJARMASIN - Rika Sylvia; Dewi Setiawati; Riski Titania (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
The purpose of this research is to find out the marketing mix that has been implemented so far at Bengkel Las Iwan Banjarmasin and to know the marketing mix that must be implemented at Bengkel Las Iwan Banjarmasin. The type of research used is descriptive qualitative, where the population in this study is all customers Bengkel Las Iwan Banjarmasin during April to June 2022 as many as 48 customers, while the sample is taken using purposive sampling as many as 30 respondent. The result of this research is that by implementing a marketing mix, to increase its income, the Iwan Banjarmasin Las Workshop can maintain product design and quality, set a fairly affordable price and provide discounted prices, place a banner or nameplate for the workshop in front of the alley where the Iwan Banjarmasin Las Bengkel is located. and promoting through social media and placing banners in public places.